EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN BERBALIK (RECIPROCAL TEACHING) DALAM PEMBELAJARAN MATEMATIKA - Ertati Ertati; Azizah Azizah (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2022)
This study aims to determine the effectiveness of mathematics learning with a reciprocal teaching model in grade VIII students in the first semester of SMP Negeri Muara Beliti, Musi Rawas Regency. The population in this study was all students of class VIII Semester I of SMP Negeri Muara Beliti, Musi Rawas Regency, which consisted of 8 classes. The sampling technique uses the cluster random sampling technique, which is sampling by means of a class draw. From the class draw it was obtained that class VIII.1 as the experimental class and class VIII.2 as the control class. Data on mathematics learning achievement is obtained using a test method in the form of an objective question. The data analysis used is a one-party t-test. The results of one party's t test showed a calculation (3,318) > ttabel (1,671) at a significant level of 5%, this means that mathematics learning achievement using reciprocal teaching methods is more effective than student learning achievement using conventional learning methods.